2018
DOI: 10.1038/s41551-018-0307-x
|View full text |Cite
|
Sign up to set email alerts
|

Implantable pre-metastatic niches for the study of the microenvironmental regulation of disseminated human tumour cells

Abstract: Cancer survivors often carry disseminated tumour cells (DTCs), yet owing to DTC dormancy they do not relapse from treatment. Understanding how the local microenvironment regulates the transition of DTCs from a quiescent state to active proliferation could suggest new therapeutic strategies to prevent or delay the formation of metastases. Here, we show that implantable biomaterial microenvironments incorporating human stromal cells, immune cells and cancer cells can be used to examine the post-dissemination pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 117 publications
1
67
0
Order By: Relevance
“…However, disadvantages of these models include off‐target effects in tissues other than the tissue of interest high development cost and time. Biomaterial scaffolds have been used to recruit tumor cells in models of breast (Aguado et al, ; Aguado et al, ; Aguado et al, ; Azarin et al, ; Carpenter, Kwak, Peyton, & Lee, ; Rao et al, ; Seib, Berry, Shiozawa, Taichman, & Kaplan, ), prostate (Bersani et al, ), ovarian (de la Fuente et al, ), melanoma (Ko et al, ), and leukemic (J. Lee et al, ) cancers. The abundance of tumor cells at a site that is readily modifiable provides a platform for probing the premetastatic and metastatic niche; however, to this point, only individual factors have been identified for their ability to enhance tumor cell abundance (Aguado et al, ; Aguado et al, ; Azarin et al, ), yet no alterations have been found that reduce tumor cell abundance relative to control, nor has the interplay between the immune microenvironment present in a scaffold and the subsequent abundance of tumor cells been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, disadvantages of these models include off‐target effects in tissues other than the tissue of interest high development cost and time. Biomaterial scaffolds have been used to recruit tumor cells in models of breast (Aguado et al, ; Aguado et al, ; Aguado et al, ; Azarin et al, ; Carpenter, Kwak, Peyton, & Lee, ; Rao et al, ; Seib, Berry, Shiozawa, Taichman, & Kaplan, ), prostate (Bersani et al, ), ovarian (de la Fuente et al, ), melanoma (Ko et al, ), and leukemic (J. Lee et al, ) cancers. The abundance of tumor cells at a site that is readily modifiable provides a platform for probing the premetastatic and metastatic niche; however, to this point, only individual factors have been identified for their ability to enhance tumor cell abundance (Aguado et al, ; Aguado et al, ; Azarin et al, ), yet no alterations have been found that reduce tumor cell abundance relative to control, nor has the interplay between the immune microenvironment present in a scaffold and the subsequent abundance of tumor cells been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Biomaterial scaffolds have been used to recruit tumor cells in models of breast Aguado et al, 2018;Aguado et al, 2015;Azarin et al, 2015;Carpenter, Kwak, Peyton, & Lee, 2018;Rao et al, 2016;Seib, Berry, Shiozawa, Taichman, & Kaplan, 2015), prostate (Bersani et al, 2014), ovarian (de la Fuente et al, 2015), melanoma (Ko et al, 2012), and leukemic (J. Lee et al, 2012) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when conditioned media from CD45 + cells from scaffold‐bearing mice was applied to tumor cell cultures, the authors observed decreased tumor cell mobility, CCL2, and increased decorin, a proteoglycan linked to reduction of metastatic spreading. These studies have influenced the development of a hydrogel‐scaffold premetastatic niche model to investigate activation of disseminated tumor cells, as well as recruitment and modulation of local immune populations . Overall, the immunomodulatory potential of scaffolds can help us understand the cancer environment, development, and dissemination, and ultimately improve cancer therapeutics.…”
Section: Localized Tam Modulation By Biomaterials: Lessons From Woundmentioning
confidence: 99%
“…These studies have influenced the development of a hydrogel-scaffold premetastatic niche model to investigate activation of disseminated tumor cells, as well as recruitment and modulation of local immune populations. [128] Overall, the immunomodulatory potential of scaffolds can help us understand the cancer environment, development, and dissemination, and ultimately improve cancer therapeutics.…”
Section: Application Of Wound Healing Principles To Cancermentioning
confidence: 99%
“…Previously, ICC scaffolds were demonstrated as enabling tools to interrogate disseminated tumor cell biology and functional engraftment of xenotransplants as implantable biomaterial niches. [62,63] In summary, ICC PNIPAM-NG scaffolds with geometrically entrapped osteospheroids mimic several structural and mechanical aspects that permits recapitulation of bone marrow niche functions, providing an environment which enables the expansion and retrieval of model hematopoietic cells via a transient temperature switch. This platform allows for continuation of the established stromal culture for repeated multicellular coculture and expansion.…”
Section: Wwwadvancedsciencenewscom Wwwadvhealthmatdementioning
confidence: 99%